Pengaruh Pendapatan Asli Daerah Dan Dana Perimbangan Terhadap Belanja Daerah Serta Keterjadian Flypaper Effect Pada Pemerintah Daerah Kabupaten Sikka Tahun Anggaran 2018-2022 - Regina Triyansi Susan; Yosefina Andia Dekrita; Konstantinus Pati Sanga (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effect of Local Original Revenue and Balancing Fund on Regional Expenditure and another purpose of this study is to determine whether there is a Flypaper Effect on the Local Government of Sikka District for Fiscal Year 2018-2022. This study used a type of causal associative research with quantitative techniques. The population of this study is the Sikka District Budget for Fiscal Year 2018-2022. The sample of this study is the Regional Budget Realization Report of Sikka District during the 2018-2022 fiscal year,the data used is in the form of secondary data. Data collection techniques use documentation methods and literature studies. Data analysis methods include descriptive statistical analysis, classical assumption tests, multiple linear regression, and hypothesis tests with t tests, F tests and multiple determination coefficient tests. The results of this study prove that partially Regional Original Revenue and Balancing Fund have no effect on Regional Expenditure. Simultaneously, Local Original Revenue and Equalization Fund have no effect on Daearh Expenditure. The test results show that the coefficient of the Balancing Fund is greater than the coefficient of Regional Original Income. This shows that there has been a Flypaper Effect on the Local Government of Sikka District during the Fiscal Year 2018-2022.